Síntese, caracterização e efeito inibitório da solução de nanopartículas de quitosana na aderência e no biofilme maduro de Streptococcus mutans - Costa, Bruna Palmeira (2015)
Introduction: Chitosan is a polymer that has, among other biological properties, antimicrobial activity against bacteria and fungi. However, the literature is still scarce concerning the clinical use of chitosan nanoparticles solution as an antibacterial agent against Streptococcus mutans biofilm. Objective: To synthesize and characterize chitosan nanoparticles solutions (ChNP) at different concentrations (0.95 mg / mL, 1.9 mg / mL and 3.8mg / mL) and evaluate their in vitro antibacterial effect on adhesion formation and reduction of S. mutans biofilm. Methodology: We performed the synthesis by ionic gelation and characterization of chitosan nanoparticles by absorption spectroscopy in the infrared (FTIR) and transmission electron microscopy (TEM). Then it was conducted the inhibition zone test and the determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against S. mutans. To analyze the antibacterial effects of ChNP, the following tests were made with the solutions concentrations in CIM, CIMx2 and CIMx4: Initial adherence: Medium with S. mutans inoculum in contact 2h with the solutions, incubation for 48 hours and plate reader; Biofilm formation: After biofilm formation of S. mutans (2h), contact 60s with the solutions, incubation for 48 hours and plate reader; Mature biofilm: For this test, it was divided 4 groups: G1: mature biofilm formation, contact 60s with the solutions in 24h and plate reader; G2: a contact 60s, every 24 hours ,for 48 hours and plate reader; G3: direct contact with the solutions for 24 hours; G4: direct contact with the solutions for 48 hours. Tests were conducted in triplicate. It was used 0.12% chlorhexidine digluconate solution as positive control and saline as negative control. Data were analyzed descriptively and by One-way ANOVA and Tukey tests (α = 0.05). Results: The results of the FTIR and TEM showed the formation of chitosan nanoparticles with an average size of 50 nm and with a rounded shape. MIC and MBC were found at a concentration of 475 mg / mL. There was growth inhibition of about 40% in the adherence in the three different concentrations and 11% in the biofilm formation after a 60s bath with the solution in CIMx4. In the mature biofilm, the percentage of inhibition of ChNP in CIMx2 and CIMx4 were from 5-7% when performed a 60s contact in 24h to 8-13% when performed a 60s contact every 24 h for 48 h and when placed in direct contact for 24 and 48 hours, the three concentrations inhibited from 90 to 100% the growth of S. mutans, a similar effect of chlorhexidine 0,12%. Conclusion: ChNP in CIM, CIMx2 and CIMx4 showed bactericidal activity against S. mutans biofilm when in continuous contact with the microorganism, remaining active for 48 hours. But when used for everyday 60s mouthwash there was minimal bacteriostatic activity of the solutions in the biofilm.